2022
DOI: 10.1038/s41598-022-13254-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional, morphological and molecular characteristics in a novel rat model of spinal sacral nerve injury-surgical approach, pathological process and clinical relevance

Abstract: Spinal sacral nerve injury represents one of the most serious conditions associated with many diseases such as sacral fracture, tethered cord syndrome and sacral canal tumor. Spinal sacral nerve injury could cause bladder denervation and detrusor underactivity. There is limited clinical experience resolving spinal sacral nerve injury associated detrusor underactivity patients, and thus the treatment options are also scarce. In this study, we established a spinal sacral nerve injury animal model for deeper unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…In addition, leukocyte migration, immune receptor activity, cytokine-cytokine receptor interaction, and Toll-like receptor signaling pathways were significantly enriched three days after BPNI, which may be related to the inflammatory response that occurs in the acute phase after bladder denervation. Li et al reported a rat model of sacral nerve injury that showed a significant increase in bladder volume and residual urine at one and four weeks after modeling [ 30 ]. PCR results showed that one week after injury, the expression of pro-inflammatory factors IL-1β, IL-6, and TNF-a in the bladder was significantly elevated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, leukocyte migration, immune receptor activity, cytokine-cytokine receptor interaction, and Toll-like receptor signaling pathways were significantly enriched three days after BPNI, which may be related to the inflammatory response that occurs in the acute phase after bladder denervation. Li et al reported a rat model of sacral nerve injury that showed a significant increase in bladder volume and residual urine at one and four weeks after modeling [ 30 ]. PCR results showed that one week after injury, the expression of pro-inflammatory factors IL-1β, IL-6, and TNF-a in the bladder was significantly elevated.…”
Section: Discussionmentioning
confidence: 99%